Adaptación antropométrica de la jaula de rocher para mejorar la eficiencia en el fortalecimiento muscular en los niños con trastornos neurológicos en la Corporación Hogar Para sus Niños de Latacunga. - Moreno Moreno, Giancarlo (2020)
Hogar para sus niños" Corporation is a non-profit organization that is dedicated to providing homes for children who are in a state of vulnerability; it is located in the southern part of Latacunga city. This project is carried out with the fundamental objective of improving the life quality of children who suffer from neurological disorders through the adaptation of a Rocher cage, which will allow the professionals of the "Casa Hogar" to have a highly qualified tool which will assist physical rehabilitation process. Rocher cage can support a weight of up to 400kg, much higher than the need of the "Casa Hogar" since the highest weight presented in children do not exceed 60kg; the suspension system is made up of 6 elastic ropes that have a maximum fatigue capacity of 50 pounds to each one of them. The Rocher cage is 200cm long and 250cm deep; these measurements were determined based on the ISO 45001 standard, which indicates the optimal conditions of the workplace. The selection of materials was made based on the standard for design, manufacture, and assembly of steel structures INEN 037. All these calculations are based on the need for the "Casa Hogar." Cost optimization of 79.98% was achieved with the construction of the Rocher cage and each of their elements that demonstrate the feasibility of the project in the economic field. The social responsibility that is fulfilled by the project was also considered, so the project is focused on a fairly vulnerable group such as children with neurological disorders.